Upaya Pembinaan Karakter Religius Peserta Didik di SMPN 3 Ampek Angkek Kabupaten Agam - Warohmah, Siti Nurlaila; Januar, Januar; Nurlina , Selfatima (Indonesian Research Journal on Education, 2023)
Era 5.0, which is an era of progress in information and communication technology in the era of theindustrial revolution, demands a culture not only of society but also students who integrate technology in their lives. in the case of Islamic Education, of course, it has experienced many impacts, both positively and negatively, one of the impacts is the emergence of new problems that will be faced, for example, the character of students who are already quite low from existing standards in accordance with the teachingsof Islam itself, it is necessary to change in order to produce a generation that is not only able to adapt to technology but can realize an advanced Islamic civilization. The purpose of this study was to look at efforts to foster the religious character of students at SMP N 3 Ampek Angkek, with this activity in fostering the religious character of students in life that reflects good behavior, besides that the existence of character education with religious values shapes the positive behavior of participants educate them to be honest, polite, respectful and appreciative. In this case the researcher uses a type of qualitative research with descriptive methods. The results of this study are efforts to build character with the religious values of students so that they have a Quranic soul and become students who have good character both in the school environment and when they are in the community environment.